(untitled) (Al-Nahrain Journal of Science, 2018)
A simple, direct, sensitive, selective and rapid spectrophotometric method is described for the determination of vanadium in foods and plants using chelate complex formation with SH (Thioglycolic acid) reagent. All parameters for the measurements were optimized and vanadium was determined at max=225.4nm. The linear concentration range obyed Beer-Lambert's low was (0.05-20)g.ml-1 for V(IV). with detection limit of 10 ng.ml-1, high sensitivity (slop = 0.1536) and linearity (r = 0.9978), good precision (%RSD at 5 g.ml-1 = 0.256 and accuracy (%Erel. = 0.59, %Rec. = 99.58). The interferences of certain elements were studied then the vanadium was determined in some foods, grains and fruits.